Predictive value of morphological features and proliferative markers (mitotic index, Ki-67, PHH3) in bronchopulmonary neuroendocrine tumors - L. M. Zakhartseva; H. Ye. Chytaieva (Patologìâ)
The aim of this study was to evaluate relations of mitotic index (MI), necrosis, IHC proliferative markers Ki-67 and PHH3, and their predictive value for lung neuroendocrine tumors (NETs) aggressiveness.